Mechanism of Attainment of the Graduate Profile for the Curricular Harmonization in the University of Atacama - Carmen Burgos Videla; Glenda Gonzales; Javiera Martinez Diaz (European Journal of Social Science Education and Research, 2024)
The progress of the curriculum redesign process promoted by the University of Atacama (UDA[1]) is presented, through the Academic Vice Rectory and operationalized by the Center for Teaching Improvement. This process has been organized with a systematic approach defined to carry out curricular innovation with a competence-based approach, guided by its Educational Model (Universidad de Atacama, 2007)[2]. This understanding shows a significant first step materialized in the mechanism of achievement of the graduate profile of which we will explain the structure, the systemic approach and the possibility of implementation through participatory strategies. It is argued that from this proposal, a change in the logic of curricular implementations and evaluations is sought at a higher level, to incorporate into the task the inclusive view regarding historicity, of the contexts in which guidelines for a sustained change that aims for quality. [1] UDA: Universidad de Atacama Acronym [2] Educational Model: Academic Commission for the elaboration of the Educational Model.